HUBUNGAN FAKTOR IKLIM DENGAN KASUS DBD DI KOTA BANDAR LAMPUNG TAHUN 2015 – 2019 - Dininta, Gilang Fitra; Hermawan, Dessy; Alfarisi, Ringgo; Farich, Achmad (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2021)
Dengue hemorrhagic fever (DHF) case in Bandar Lampung City shows an increasing trend of cases. In 2014, the number of cases was 389 cases; by the end of 2018, it had increased to 1,114 cases. Climatic factors are thought to have contributed to the increase in cases. This study aims to determine the relationship between climate factors and the number of dengue cases in 2015-2019. The study used secondary data with a cross-sectional design. Data were obtained from the Bandar Lampung City Health Office and the Meteorology, Climatology, and Geophysics Agency (BMKG). Univariate analysis with Mean, Median, Minimum-Maximum. The Kolmogorov-Smirnov test was carried out to determine the normality of the data, followed by bivariate analysis with Pearson Correlation and Spearman's Rank. Multivariate analysis was performed with Linear Regression by considering the regression assumption. The study found that more dengue cases were in January, February, March. A negative correlation was shown between temperature and the incidence of DHF (r=-0.274; p-value=0.038), and a positive correlation with humidity (r=0.390; p-value=0.002), and rainfall (r=0.370; p-value= 0.005). Air humidity and rainfall affect the number of dengue cases, respectively 33.0% and 30.5%. The results of this study have provided evidence of a relationship between climate factors and cases of DHF. It is hoped that this can be an input for the prevention and control of dengue fever.